Critical reflections on Stanley Hauerwas' theology of disability : disabling society, enabling theology - Hauerwas, Stanley, 1940-; Swinton, John, 1957- (Haworth Pastoral Press, 2004)
?No other mainstream theologian has so consistently and trenchantly taken a stand with and for people with developmental disabilities.??John SwintonCritical Reflections on Stanley Hauerwas' Theology of Disability: Disabling Society, Enabling Theology examines the influential writings of one of the most important contemporary theologians. Over the past thirty years, Time magazine Theologian of the Year (2001) Dr. Stanley Hauerwas has consistently presented a theological position which values the deep theological significance of people with developmental disabilities, as well as thei.